HOW TO BE A GOOD LANGUAGE TEACHER - Saadillah, Saadillah (LET: Linguistics, Literature and English Teaching Journal, 2012)
AbstractThere are two  crucial questions about the study of language  teacher. The first  question is ?How is a good   teacher?? The second question is ?How is a good language teacher?  To answer those questions, it should be understood that teacher is a usual creation of God. Like an English proverb says?there is no one  perfect  so, the teacher maybe will do the mistakes. The teacher maybe has some weakness .  This writing tries describing some facts about teachers as general, and introducing the  reader about how is going to be a good language teacher.